Radiochemical and biological assessments of a PSMA-I&S cold kit for fast and inexpensive 99mTc-labeling for SPECT imaging and radioguided surgery in prostate cancer - Fuscaldi, Leonardo Lima; Sobral, Danielle Vieira; Durante, Ana Claudia Ranucci; Mendonça, Fernanda Ferreira; Miranda, Ana Cláudia Camargo; Salgueiro, Carla; de Castiglia, Silvia Gomez; Yamaga, Lilian Yuri Itaya; da Cunha, Marcelo Livorsi; Malavolta, Luciana; de Barboza, Marycel Figols; Mejia, Jorge (Frontiers in Chemistry, 2023)
The expression of prostate-specific membrane antigen (PSMA) is upregulated in prostate cancer (PCa) cells and PSMA-ligands have been radiolabeled and used as radiopharmaceuticals for targeted radionuclide therapy (TRT), single photon emission computed tomography (SPECT) or positron emission tomography (PET) molecular imaging, and radioguided surgery in PCa patients. Herein, we aimed at radiolabeling the PSMA-I&S cold kit with 99mTc, resulting in a radiopharmaceutical with high radiochemical yield (RCY) and stability for SPECT imaging and radioguided surgery in PCa malignancies. Various pre-clinical assays were conducted to evaluate the [99mTc]Tc-PSMA-I&S obtained by the cold kit. These assays included assessments of RCY, radiochemical stability in saline, lipophilicity, serum protein binding (SPB), affinity for LNCaP-PCa cells (binding and internalization studies), and ex vivo biodistribution profile in naive and LNCaP-PCa-bearing mice. The radiopharmaceutical was obtained with good RCY (92.05 ± 2.20%) and remained stable for 6 h. The lipophilicity was determined to be -2.41 ± 0.06, while the SPB was ~97%. The binding percentages to LNCaP cells were 9.41 ± 0.57% (1 h) and 10.45 ± 0.45% (4 h), with 63.12 ± 0.93 (1 h) and 65.72 ± 1.28% (4 h) of the bound material being internalized. Blocking assays, employing an excess of unlabeled PSMA-I&S, resulted in a reduction in the binding percentage by 2.6 times. The ex vivo biodistribution profile confirmed high accumulation of [99mTc]Tc-PSMA-I&S in the tumor and the tumor-to-contralateral muscle ratio was ~6.5. In conclusion, [99mTc]Tc-PSMA-I&S was successfully obtained by radiolabeling the cold kit using freshly eluted [99mTc]NaTcO4, exhibiting good RCY and radiochemical stability. The preclinical assays demonstrated that the radiopharmaceutical shows favorable characteristics for SPECT imaging and radioguided surgery in PCa patients.